OPTIMALISASI CRM @ BRANCH SEBAGAI SALAH SATU LANGKAH MEWUJUDKAN BANK MANDIRI MENJADI THE SERVICE LEGEND - Pipin Sukandi; Heru Rizky Jiwayani (Bina Ekonomi, 2010)
Based on the monitor service quality, for the second consecutive year, Mandiri Bank version of Marketing Research lndonesia (MRI) and the Bureau of Research lnfobank of "The Best Bank Service Excellence". Successfully defend the title which was achieved in 2007/2008 and 2008/ 2009 was really very proud. tt is not released from the implementation of Exellence Service, which a/so has been applied by Mandiri Bank. Excellent Service certainly not enough to just be a paradigm and skills off frontline or frontliners in serving customers, but it requires sincerity, and high commitment from every part of the organization, especially at top management. Excellent Service should also be reduced to a structured steps that are implemented in every function in the banking company' We would often hear the term much more difficult to maintain than grab especially for those who have been our competitors ahead of excellence in service and will certainly try harder than ever. To service our customers' expectations also increased because the customer already understands that Mandiri Bank is the Best Service Excellence ln addition to increased expectations, customers now also getting spoiled Everything is served to suit his wants. The things above would be a great challenge for us to continuously improve our faults and seek continuous improvement in service excellence, lt also is not just to improve ratings, but according to the direction of Directors, so we became The Service Legend. Predicate The Service Legend will make people always and always remember when talking about the Mandiri Bank, bank services in lndonesia. The Service Legend is more than just number one. So everyone connected with the bank, when asked about the service, will be called Mandiri Bank. Many steps/measures to be implemented independent Bank of The Service Legend them with services that are supported by information systems and technology' hence made an application system that can meet customers' needs and facilitate the activities of service to its customers @ Branch Customer Relationship Management (CRM @ Branch). CRM @ Branch is a tool for front liners to improve service and sales from anywhere with the same price and standard. CRM @ Branch provides information on the customer, all products and services utilized by customers in a single system with an accurate and consistent information in the form of product literature for the need for cross selling. CRM is available in the facility to record every activity of non-financial interaction with customers online and realtime, as well as financial transactions that have been available bankwide, online and realtime. CRM @ Branch helped frontliner doing sales and increase cross selling and referral by digging profile customer data, monitor progress of sales and customer complaints that can be solved once and for all and measurable. The more we succeed in doing cross-selling, the better Contribution Margin & KPI Mandiri Bank branches. With the CRM @ Branch, is expected to service and sales effectiveness processes in frontliner can increase, so the value of product sales increased Mandiri, handling complaints from customers more quickly, and coordination among units to be getting better. CRM lmplementation @ Branch as a consistent infrastructure used by the best banks in the world, supporting enhanced functions in the ranks of sales and service branches of Mandiri Bank. In relation to the implementation of CRM @ Branch, there are 3(three) things that must be considered: 1) Associated with the human implementation will be successful if people know the purpose of CRM programs @ Branch, namely Mandiri Bank should outperform the market ,in association with branches, service and sales of Mandiri Bank to be the best. 2) lt is a very human question of what the benefit for the Branch? The achievement of its targets relating to the achievement of course goals, rewards, and incentives. If the CRM tools @ Branch implemented, could improve the quality of service frontliners to customers, help us increase the value of MRI branches and very helpful frontliners in doing cross selling. The more success/a/ we are doing cross selling, the better Contribution Margin KPI branch & branch. 3) We must be diligent and disciplined use of this CRM system @ Branch. Many big hanks that failed to gain maximum benefit from CRM systems @ Branch, because of its human undisciplined use of this system.